EFFECT OF CURING REGIMES ON THE COMPRESSIVE STRENGTH OF FLY ASH–GGBS BASED GEOPOLYMER CONCRETE INCORPORATING RECYCLED AGGREGATES - Pooja S M; Supritha M Y; Harish Ram (International Educational Journal of Science and Engineering, 2026)
The curing regime plays a critical role in the strength development of geopolymer concrete (GPC), particularly when incorporating industrial by-products and recycled aggregates. This study investigates the influence of different curing methods on the compressive strength of fly ash–GGBS based geopolymer concrete with partial replacement of natural coarse aggregates by recycled aggregates. Three curing conditions—ambient curing, oven curing, and hot water curing (accelerated curing)—were adopted to evaluate their effect on strength development. Concrete mixes with a constant binder composition and alkaline activator ratio were prepared and tested for compressive strength at 7 and 28 days. The results indicate that accelerated curing methods significantly enhance early-age strength due to improved geopolymerization kinetics, with oven curing exhibiting the highest strength at both ages, followed by steam curing, while ambient curing showed slower but continuous strength development over time. The incorporation of recycled aggregates resulted in a marginal reduction in compressive strength; however, the values remained within acceptable structural limits. Overall, the study highlights that appropriate curing strategies can effectively optimize the performance of sustainable geopolymer concrete, making it a viable alternative for structural applications.